2011
DOI: 10.1091/mbc.e11-01-0055
|View full text |Cite
|
Sign up to set email alerts
|

Nab2 functions in the metabolism of RNA driven by polymerases II and III

Abstract: The hnRNP Nab2 is associated with actively transcribed RNAPII and RNAPIII genes. Nab2 has a function in RNAPII transcription and participates in tRNA metabolism and ribosomal subunit export, and, as a consequence, nab2 mutations confer translation defects. Results support Nab2 as a key regulator of gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 51 publications
5
38
0
Order By: Relevance
“…In a recent study, we determined the genome-wide occupancy of Nab2 and other nuclear mRNP components in S. cerevisiae by ChIP-chip (Meinel et al 2013). As expected, Nab2 occupies protein-coding genes (Gonzalez- Aguilera et al 2011;Meinel et al 2013). However, we discovered that, in addition to RNAPII transcribed genes, Nab2 also localizes to genes transcribed by RNAPIII.…”
Section: Nab2 Is Recruited To Rnapiii Genesmentioning
confidence: 67%
“…In a recent study, we determined the genome-wide occupancy of Nab2 and other nuclear mRNP components in S. cerevisiae by ChIP-chip (Meinel et al 2013). As expected, Nab2 occupies protein-coding genes (Gonzalez- Aguilera et al 2011;Meinel et al 2013). However, we discovered that, in addition to RNAPII transcribed genes, Nab2 also localizes to genes transcribed by RNAPIII.…”
Section: Nab2 Is Recruited To Rnapiii Genesmentioning
confidence: 67%
“…At present, very little is known about how members of the dNab2/ZC3H14 family of proteins are recruited to nascent transcripts. As mentioned above, a recent study found that yeast Nab2 associates with RNA polymerase II genes in a transcription-dependent manner, 18 and studies in yeast also suggest that Nab2 can interact with the vast majority of poly(A) RNAs. 54 Although most mRNA transcripts should be polyadenylated and therefore theoretically bound by dNab2/ZC3H14, other proteins bound to sequences within the 3' UTR of specific transcripts could also preferentially recruit dNab2/ZC3H14 to specific transcripts.…”
mentioning
confidence: 80%
“…While Pab proteins are typically associated with regulation of mRNAs, there is growing evidence that other types of RNAs also require Pabs for proper regulation. 17,18 The identity of the RNAs or classes of RNAs impacted disability, [13][14][15] is expressed at lower levels in the hippocampus (and specifically the dentate gyrus), perhaps suggesting that disruption of ZC3H14 and FMR1 may impact different cell types in hippocampal circuitry.…”
Section: Members Of a Family Of Znf-containing Pabs Perform Conservedmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, initiation factors must be exchanged for elongation factors [15], which are thought to increase the transcription rate and RNAPII processivity. In fact, recently, there has been an extraordinary increase in the number of proteins known to influence transcription elongation by avoiding transcriptional arrest, facilitating chromatin passage and mRNA processing [16][17][18][19][20][21], allowing mRNA packaging into a mature ribonucleoprotein (mRNP) and controlling mRNP quality and mRNA export [13,[22][23][24][25][26][27][28]. Therefore, the discovery of all of these factors has provided further evidence that the elongation phase is also highly regulated in eukaryotic cells and strictly coordinated with other nuclear processes [12][13][14].…”
Section: Introductionmentioning
confidence: 99%